Obstructive sleep apnea and chronic pain as risk factors of cognitive impairment in elderly population: A study from Indonesia - Tiara Tiara; Fidiana Fidiana (Narra Sains Indonesia, 2021)
Obstructive sleep apnea (OSA), one of the most prevalent sleep-related breathing disorders in the elderly, seems to be underdiagnosed. Meanwhile, the resulting complication on cognitive function could impact on patient’s quality of life. Association between OSA and cognitive function in the elderly varies highly, depending on study type, setting, and possibly by demographic differences. Therefore, this study sought to determine the risk of OSA among elderly and to assess the association of OSA risk and other plausible factors with cognitive function. In this cross-sectional study, patients aged 60 years and above who visited the outpatient clinic at two main hospitals in Surabaya of Indonesia were examined. A total of 178 participants were interviewed to evaluate the OSA risk using STOP-Bang questionnaire, the cognitive dysfunction using Montreal Cognitive Assessment Indonesian version (MoCA-Ina), depressive symptoms using Geriatric Depression Scale-15 (GDS-15), and sleep disorder using Insomnia Screening Questionnaire (ISQ). The Mann-Whitney and Chi-square tests were used to assess factors associated with cognitive impairment. In addition, logistic regression analyses were performed to evaluate the role of high risk of OSA on cognitive impairment. A total of 120 patients were considered having high risk of OSA (STOP-Bang score ≥3), and 129 had mild cognitive impairment (MCI) (MoCA-Ina <26). Among the elderly who had high risk of OSA, 94 were diagnosed with MCI (78.3%). Multivariate logistic regression analysis showed that high risk of OSA (OR: 2.99; 95%CI: 1.39, 6.46, p=0.005), chronic pain (OR: 5.53; 95%CI: 1.19, 25.64, p=0.029), and low education level (OR: 4.57; 95%CI: 1.79, 11.63) were associated with MCI. In conclusion, our data suggests a high prevalence of MCI among high risk OSA elderly. Screening and comprehensive management might be beneficial to improve or to preserve cognitive function in elderly group.